One - Dimensional Man / Studies in the Ideology of Advanced Industrial Society - Marcuse Herbert (Rouledge, 1991)
Marcuse's best-selling work to another generation of readers in the context of contemporary events. Acknowledgements, Introduction, One Dimensional Society, The New Forms of Control, The Closing of the Political Universe, The Conquest of the Unhappy Consciousness: Repressive Desublimation, The Closing of the Universe of Discourse, One-Dimensional Thought, Negative Thinking: The Defeated Logic of Protest, From Negative to Positive Thinking: Technological Rationality and the Logic of Domination, The Triumph of Positive Thinking: One-Dimensional Philosophy, The Chance of the Alternatives, The Historical Commitment of Philosophy, The Catastrophe of Liberation, Conclusion, Index.